OPTIMALISASI TELEMEDICINE OLEH TENAGA KESEHATAN DI FASILITAS PELAYANAN KESEHATAN PRIMER - Widya Ratna Wulan; Evina Widianawati; Ika Pantiawati (Indonesian Journal of Health Information Management Services, 2023)
The lack of health communication technology literacy in the elderly group affects the high mortality rate due to non-communicable diseases. Health communication and information technology media can be a medium for health workers and elderly participants such as telemedicine but there are still limitations in device use. This activity aimed to educate and socialize the concept of telemedicine applications to health workers and participants able to be independent in facilitating the community regarding health issues, especially the risk of Hypertension and Diabetes Mellitus. The implementation focused on empowering participants in the Elderly Chronic Disease Management Program and health workers in Primary Health Care Facilities in Semarang Regency with sub-activities of Communication Techniques Training and Socialization of Prolanis Telemedicine Applications to Health Workers and Elderly Participants. The results of the service show that health workers who are responsible for Prolanis activities understand the importance of communication with participants through health digitization and data recording for participants through health technology media. Participants found this application useful for communication systems and data collection, and hope it will be further developed and re-socialized.